Creation of high-yielding salt-tolerant wheat varieties on saline soils in the territory of the Republic of Azerbaijan - Maya A. Khanisova ,Konul R. Tagiyeva,Atabay A. Jahangirov,Ibrahim V. Azizov (South Eastern European Journal of Public Health, 2025)
In the selection work carried out to obtain salt-tolerant wheat varieties, (F4) and (F5) generation hybrid forms were planted and cultivated in different years under different ecological conditions. These hybrids were mainly planted in normal soil areas of the Garabagh Scientific Research Base of the Tartar region, as well as in saline soil areas of the Ujar region of the Soil Science Institute in 2022 and 2023. In the saline soils of Ujar region, sulfates were mainly (Na2SO4) 1.5%. After the grain ripening stage of vegetation was completed, the yield indicators of hybrid forms cultivated under normal conditions and in saline soils were comparatively studied according to the main structural elements of the spike, the weight of the spike, the grain and the number of grains. The yield indicators were calculated according to the tolerance index and the hybrids with less yield loss were evaluated as relatively salt-resistant. Thus, Gobustan x Sheki-1, Dagdash x Murov, Vugar x Barakatli -95, Qirmizi Gul-1 x Tale-38, Mirbashir-50 x Shiraslan-23. Barakatli-95 x Gobustan, Karabakh x Mirbashir-128, Karabakh-x Sharq showed more resistance than other hybrid forms in terms of yield indicators.